Clinical quality and performance measurement in the prehospital emergency medical services in the low-to-middle-income country setting : developing clinical quality and performance indicators as a measure of care in South Africa - Howard, Ian (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.